The Role of The Women's Organization of Nahdlatul Ulama (NU) in Efforts to Control Cigarette Consumption in Indonesia - Nadya, Salsabila; Sihombing, Isranalita Madelif (UI Scholars Hub, 2023)
Background: The protection of the nation's next generation from the dangers of smoking cannot be separated from the role of women/mothers as educators and as influencers in creating a safe and comfortable environment from exposure to cigarette smoke for children to grow and develop healthily. Aims: To analyze the role of the Nahdlatul Ulama (NU) women's organization, namely NU Young Women's Organization (Fatayat NU) and NU Female Student Association (IPPNU) in efforts to control tobacco in Indonesia. Methods: This research is descriptive research with a method of collecting data on the results of activities owned by the Center for Social Security Studies, University of Indonesia (PKJS-UI) for 2019-2023, and the data is presented in the form of narrative points and tables of activity results which attach links as outputs of activity results. Results: The role of NU has an impact on increasing public awareness, empowering women, and influencing policy. However, it still has challenges from a cultural, political, economic, and educational perspective. Conclusion: Although still facing various challenges, NU has a role as a campaigner, educator, and advocate who has a positive impact on tobacco control efforts in Indonesia.